Mr. Putter & Tabby : Bake the cake - Rylant, Cynthia; Howard, Arthur (San Diego : Harcourt, 2004)
Mr. Putter and his cat, Tabby, stay up all night when he decides to bake his neighbor, Mrs. Teaberry, a cake for Christmas, even though he has never baked a cake before.
Elem. School Library Collection
Horn Book Starred
School Library Journal
Booklist, August 2004
Elem. School Library Collection, June 2000
Horn Book Starred, December 2003
Keywords: Cake -- Juvenile fiction; Christmas -- Juvenile fiction; Gifts -- Juvenile fiction; Cake -- Fiction; Christmas -- Fiction; Gifts -- Fiction; Cake -- Fiction; Christmas -- Fiction; Gifts -- Fiction